A five-year prospective evaluation of anticholinergic cognitive burden and falls in the Malaysian elders longitudinal research (MELoR) study. (January 2022) - Xu, Xiang Jiang; Myint, Phyo Kyaw; Kioh, Sheng Hui; Mat, Sumaiyah; Rajasuriar, Reena; Kamaruzzaman, Shahrul Bahyah; Tan, Maw Pin
Highlights: The use of drugs with possible or mild anticholinergic properties is more common compared to those with strong anticholinergic properties. The use of drugs with possible or mild anticholinergic properties is associated with falls cross-sectionally. Only individuals with a cumulative anticholinergic cognitive burden score of three and above were at increased risk of falls at two-year follow-up. The mechanisms underlying the long-term risk associated with cumulative anticholinergic use remains unclear. Future studies should identify effective strategies to reduce anticholinergic use and whether this will lead to reduced risk of falls prospectively. Abstract: Background: While anticholinergic use is associated with stroke, dementia and mortality, few have evaluated its potential link with falls. To determine the relationship between anticholinergic cognitive burden (ACB) and falls over five years using the Malaysian Elders Longitudinal Research (MELoR). Methods: Community-dwelling adults aged 55 years and over were recruited through electoral roll sampling. Data obtained at baseline and follow-up (FU) at two and five years were included. Falls in the preceding 12 months were recorded. Results: Of the 1499 individuals (mean (SD) age= 68.9(7.5) yrs and 53.3% female) with information on baseline ACB exposure, 575(38.4%) had ACB scores of 1-2 and 117(7.8%) had ACB scores ≥ 3 . Differences in age, ethnicity, smoking status, diabetes, hypertension, cardiovascular disease, arthritis and education existed between ACB groups. Fall occurrence differed between ACB groups at recruitment ( p = 0.004) and 2-year FU ( p = 0.001) but not at 5-year FU ( p = 0.053). Logistic regression revealed an independent association between ACB 1-2 and falls at baseline (odds ratio, OR (95% confidence interval, CI) =1.412(1.035-1.926)) and ACB ≥ 3 and falls at 2-yr FU (OR (95%CI) =2.098(1.032-4.263)) following adjustment for confounders. Conclusion: Low level exposure to drugs with anticholinergic properties was associated cross-sectionally with falls, while exposure to higher levels were prospectively associated with falls at 2-year but not at 5-year FU. Future studies should determine whether avoidance of drugs with anticholinergic effects will lead to reduction in falls.